The Existence of Ludruk Show Behind The Popular Art Industry - Heny Purnomo (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2021)
The presence of popular art is described by the rapid growth anddevelopment of television medium influence the life of performingarts and the production activityin the show. Covid-19 and postpandemic activity also have an impact on art performance. Thecreative activity of traditional theater community are stagnating now,so that affecting the existence of show and leaving many problems.The development of popular art in ludruk show as a traditional theaterhas created a transformation of space and time as well as the aestheticvalue in it. When the institution as a